EFISIENSI KINERJA SEBELUM DAN SAAT PANDEMI COVID-19 PADA PRODUK PEMBIAYAAN (Studi Pada PT. Mandiri Utama Finance) - Zaiz Fisabilillah; Suryani; Efi Syarifudin (Wahana Islamika Jurnal Studi Keislaman, 2023)
Companies face challenges in achieving efficiency levels during the Covid-19 pandemic. Efficiency is a benchmark in measuring a company's financial performance. The DEA method as a non-parametric approach is used to measure the efficiency of PT. Mandiri Utama Finance. In this research, the research variable is the input variable consisting of Total Assets, Equity and Liabilities. Output Variables consist of Operating Income and Consumer Financing. Testing with the CRS model shows that the efficiency value in 2017 was 94.92% meaning it was not efficient, 2018 was 100% meaning it was efficient, in 2019 it dropped to 97.86% meaning it was not efficient. In 2020 and 2021 both get 100% meaning achieving efficiency. As for testing with the VRS model, the efficiency value from 2017 to 2018 obtained 100% meaning efficient, in 2019 it decreased to 98.83% which means inefficient and in 2020-2021 PT Mandiri Utama Finance achieved an efficiency value of 100% the same as the results of the CRS model. Based on DEA calculations on both the CRS and VRS models which show differences during the pandemic and before the pandemic, namely before the 2017-2019 pandemic, PT. Mandiri Utama Finance is not in a perfectly efficient position, in contrast to 2020-2021, where in that year a pandemic was occurring in Indonesia, which actually scored 100%.